Antibody responses after COVID-19 infection in patients who are mildly symptomatic or asymptomatic in Bangladesh. (December 2020) - Shirin, Tahmina; Bhuiyan, Taufiqur Rahman; Charles, Richelle C.; Amin, Shaheena; Bhuiyan, Imran; Kawser, Zannat; Rahat, Asifuzaman; Alam, Ahmed Nawsher; Sultana, Sharmin; Aleem, Md Abdul; Khan, Manjur Hossain; Khan, Samsad Rabbani; et al.
Highlights: Serum IgG developed in 95% mildly symptomatic patients by day 14 and all seroconverted by day 30. Serum IgM and IgA antibody responses were lower and less frequent than corresponding IgG responses. Serum IgM and IgA responses peaked and declined earlier in 100% of mild symptomatic individuals. <45% of asymptomatic infected individuals had seroconverted by day 30 post-PCR diagnosis. Impact on modeling of herd immunity. Abstract: Objectives: Studies on serological responses following coronavirus disease-2019 (COVID-19) have been published primarily in individuals who are moderately or severely symptomatic, but there are few data from individuals who are mildly symptomatic or asymptomatic. Methods: We measured IgG, IgM, and IgA to the receptor-binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by using enzyme-linked immunosorbent assay in mildly symptomatic (n = 108) and asymptomatic (n = 63) on days 1, 7, 14, and 30 following RT-PCR confirmation in Bangladesh and when compared with pre-pandemic samples, including healthy controls (n = 73) and individuals infected with other viruses (n = 79). Results: Mildly symptomatic individuals developed IgM and IgA responses by day 14 in 72% and 83% of individuals, respectively, while 95% of individuals developed IgG response, and rose to 100% by day 30. In contrast, individuals infected with SARS-CoV-2 but who remained asymptomatic developed antibody responses significantly less frequently, with only 20% positive for IgA and 22% positive for IgM by day 14, and 45% positive for IgG by day 30 after infection. Conclusions: These results confirm immune responses are generated following COVID-19 who develop mildly symptomatic illness. However, those with asymptomatic infection do not respond or have lower antibody levels. These results will impact modeling needed for determining herd immunity generated by natural infection or vaccination.